2021
DOI: 10.24059/olj.v25i4.2440
|View full text |Cite
|
Sign up to set email alerts
|

“We Overwhelm Them with Hope”: How Online Mentors Can Support Online Learners

Abstract: This survey research study analyzed responses from 143 mentors from around the world participating in a global higher education initiative. Results confirmed the effectiveness of four mentoring domains identified in the literature, reporting the most success from providing emotional and psychological support for students. This article provides mentoring strategies including student goal setting, identifies characteristics of an online role model, and shows the importance of online mentors’ confidence in studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, online group supervision can be integrated into psychology graduate programs as part of the curriculum, especially in times of crises when there are challenges of isolation and distance. However, moving from the "circle" of the in-person group to the squares of the screen requires specific knowledge, and higher education institutions should prepare their teachers to teach and supervise online (Andersen & West, 2021). For example, supervisors may be encouraged to assume a role as facilitators of the group as a whole while helping members tolerate conflict, embracing vulnerability, and discussing clear goals and tasks for the group.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Moreover, online group supervision can be integrated into psychology graduate programs as part of the curriculum, especially in times of crises when there are challenges of isolation and distance. However, moving from the "circle" of the in-person group to the squares of the screen requires specific knowledge, and higher education institutions should prepare their teachers to teach and supervise online (Andersen & West, 2021). For example, supervisors may be encouraged to assume a role as facilitators of the group as a whole while helping members tolerate conflict, embracing vulnerability, and discussing clear goals and tasks for the group.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Previous ODL reviews (Lee & Choi, 2011;Rotar, 2020) have identified inadequate preparation, among other factors, as a contributor to feeling anxious or fearful, and suggested that students should be holistically supported (Jacklin & Le Riche, 2009). Indeed, emotional and psychological support can play an important role in student success (Andersen & West, 2021) and facets of students' emotional engagement has been linked with achievement-related outcomes via cognitive and behavioural engagement (Fredricks et al, 2004). Thus, it is important that ODL providers also attend to the affective experiences of students.…”
Section: Emotional Engagementmentioning
confidence: 99%